Sudden fear - Elwood, Roger (Dallas : Word Pub., 1991)
The teenage sons of an American diplomat find their lives in danger when they intercept a terrorist's message.
"Word kids!"
Keywords: Brothers; Terrorism; Adventure and adventurers; Christian life